Effect of dental surface treatment with Nd:YAG and Er:YAG lasers on bond strength of resin composite to recently bleached enamel - Gomes Torres, Carlos Rocha [UNESP]; Ferraz Caneppele, Taciana Marco [UNESP]; de Lazari, Regina Del Moral [UNESP]; Ribeiro, Carolina Ferraz [UNESP]; Borges, Alessandra Buhler [UNESP] (Springer London Ltd, 2012)
The aim of this work is to evaluate the effect of surface treatment with Er:YAG and Nd:YAG lasers on resin composite bond strength to recently bleached enamel. In this study, 120 bovine incisors were distributed into two groups: group C: without bleaching treatment; group B: bleached with 35% hydrogen peroxide. Each group was divided into three subgroups: subgroup N: without laser treatment; subgroup Nd: irradiation with Nd:YAG laser; subgroup Er: irradiation with Er:YAG laser. The adhesive system (Adper Single Bond 2) was then applied and composite buildups were constructed with Filtek Supreme composite. The teeth were sectioned to obtain enamel-resin sticks (1 x 1 mm) and submitted to microtensile bond testing. The data were statistically analyzed by the ANOVA and Tukey tests. The bond strength values in the bleached control group (5.57 MPa) presented a significant difference in comparison to the group bleached and irradiated with Er:YAG laser (13.18 MPa) or Nd:YAG (25.67 MPa). The non-bleached control group presented mean values of 30.92 MPa, with statistical difference of all the others groups. The use of Nd:YAG and Er:YAG lasers on bleached specimens was able to improve the bond strengths of them.
Keywords: Bleaching; Microtensile bond strength; Nd:YAG laser; Er:YAG laser